HUKUM KEWARISAN DI INDONESIA: Studi Komparatif antara Kompilasi Hukum Islam dengan Kitab Undang-Undang Hukum Perdata - Lusiana, Vinna (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Inheritance law in the Compilation of Islamic Law (KHI) and the Civil Code (KUHPer) are two written laws that regulate the division of inheritance in Indonesia. The KHI applies to Muslims, while the KUHPer applies to non-Muslims. The differences in these provisions pose challenges and complexities in enforcing inheritance law in Indonesia. This study utilizes library research with a juridical-normative method. The author found that Islamic inheritance provisions are contained in Articles 171-193, 209-214, based on the provisions of Surah Al-Nisā’ verses 7, 11, 12, 33, and 176. On the other hand, the KUHPer is regulated in Articles 839-1149. Regarding inheritance acquisition, the KHI regulates it in the form of inheritance acquisition by children, fathers and mothers, widowers and widows, and inheritance acquisition by siblings with predetermined portions in the KHI. Meanwhile, the KUHPer divides it into two major groups, namely lawful heirs without illegitimate children recognized legally and lawful heirs together with recognized illegitimate children. These differences in inheritance provisions provide clarification, regulations, dispute resolution, child protection, and harmony to raise public awareness of inheritance rules.